2013
DOI: 10.1039/c3ob41044g
|View full text |Cite
|
Sign up to set email alerts
|

Copper catalyzed synthesis of fused benzimidazolopyrazine derivatives via tandem benzimidazole formation/annulation of δ-alkynyl aldehyde

Abstract: A novel route to synthesize the biologically active benzimidazolopyrazine core is outlined. The reaction proceeds via tandem benzimidazole formation/annulations of indole, pyrrole and aliphatic δ-alkynyl aldehydes in the presence of copper salts and green solvents with moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It should also be noted that the involvement of single electron transfer processes can not be excluded. 37 Finally, unlike what was reported by Nagarajan, 38 the reaction of ophenylenediamine with aldehydes in the presence of copper salt only showed no formation of benzimidazole derivatives in appreciable yields in the reaction mixture. At the same time, no Cu(0) powder was observed on the glass bottom of the reaction flask as further confirmation that single electron redox changes of copper are not involved in the reaction.…”
Section: Resultsmentioning
confidence: 74%
“…It should also be noted that the involvement of single electron transfer processes can not be excluded. 37 Finally, unlike what was reported by Nagarajan, 38 the reaction of ophenylenediamine with aldehydes in the presence of copper salt only showed no formation of benzimidazole derivatives in appreciable yields in the reaction mixture. At the same time, no Cu(0) powder was observed on the glass bottom of the reaction flask as further confirmation that single electron redox changes of copper are not involved in the reaction.…”
Section: Resultsmentioning
confidence: 74%
“…We chose the bisindole 5a as a model substrate to optimize the reaction condition (Table 2). In our previous work, 18 we found that copper salts are suitable for intramolecular electrocyclization reactions. We began the optimization reaction with copper(I) iodide in acetonitrile at room temperature.…”
Section: Syn Thesismentioning
confidence: 96%
“…Many metals such as gold, 6 silver, 7 iron, 8 gallium, 9 mercury, 10 indium, 11 palladium, 12 platinum, 13 ruthenium, 14 or tungsten, 15 as well as Brønsted acids 16 and thermal rearrangement, 17 have been used to promote intramolecular hydroarylation reactions. As part of our search for new metal catalysts, and in continuation of the development of our copper-catalyzed intramolecular electrocyclization reaction, 18 we report a copper-catalyzed intramolecular hydroarylation reaction of an N-propargyl group for the synthesis of β-carboline derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concisely, diverse functionalized substituted benzimidazole derivatives 30–38 have been synthesized in moderate to high yields by reaction of susbstituted‐ o ‐phenylenediamine with benzaldehyde and heteroaromatic aldehyde derivatives in the presence of heterogeneous catalysts such as Cu(II) containing nanosilica for the synthesis of 30 , ZrO(NO 3 ) 2 for 31 , nano CeO 2 for 32 , CuI for 33 , 3,6‐di(pyridin‐4‐yl)‐1,2,4,5‐tetrazine for 34 , NaHSO 3 /H 2 O 2 for 35 , SO 4 2− –ZrO 2 for 36 , Na 2 S 2 O 5 for 37 , and Na 2 S 2 O 4 for 38 (Table ).…”
Section: Chemistrymentioning
confidence: 99%